Unraveling credit risk determinants: Empirical evidence from Indonesian Regional Development Banks - Tias Retnani; Wisnu Mawardi (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study examines the determinants of credit risk, proxied by non-performing loans (NPLs), in Regional Development Banks (RDBs) in Indonesia over the period 2017–2022, covering 480 observations. Using panel regression analysis and robustness tests based on regional classifications and pre- and during-pandemic periods, the findings reveal that capital adequacy (CAR), profitability (ROA), income diversification (PSB), and bank size significantly contribute to reducing credit risk. However, the effectiveness of these factors is contingent upon external conditions and regional characteristics. During the COVID-19 pandemic, only capital adequacy and bank size remained robust in mitigating credit risk, while the effects of profitability and income diversification weakened. Furthermore, the results indicate heterogeneity in credit risk behavior between BPDs operating in Java and those outside Java, suggesting the importance of region-specific dynamics. This study contributes to the literature by providing evidence from an emerging market context and highlighting the conditional role of internal bank factors under varying economic conditions. The findings imply that strengthening capital buffers and enhancing operational efficiency should be prioritized in credit risk management, alongside the development of more adaptive and context-sensitive risk management frameworks.